2022
DOI: 10.1039/d1fo03520g
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic strains alleviated OVA-induced food allergy in mice by regulating the gut microbiota and improving the level of indoleacrylic acid in fecal samples

Abstract: Food allergy (FA) is a common immune disorder caused by food antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
5
28
0
Order By: Relevance
“…Interestingly, LTA increased the gut microbiota diversity and enhanced Th1 immune response in the present study. Furthermore, the gut microbiota and its short-chain fatty acid metabolites can alleviate OVA-A pathological symptoms by decreasing Th2 immune responses . LTA contributes to intestinal homeostasis by regulating short-chain fatty acid metabolism; therefore, the potential activity of LTA in regulating gut microbiota and intestinal immunity has attracted much attention .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, LTA increased the gut microbiota diversity and enhanced Th1 immune response in the present study. Furthermore, the gut microbiota and its short-chain fatty acid metabolites can alleviate OVA-A pathological symptoms by decreasing Th2 immune responses . LTA contributes to intestinal homeostasis by regulating short-chain fatty acid metabolism; therefore, the potential activity of LTA in regulating gut microbiota and intestinal immunity has attracted much attention .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the gut microbiota and its short-chain fatty acid metabolites can alleviate OVA-A pathological symptoms by decreasing Th2 immune responses. 42 LTA contributes to intestinal homeostasis by regulating short-chain fatty acid metabolism; therefore, the potential activity of LTA in regulating gut microbiota and intestinal immunity has attracted much attention. 24 LTA intervention was found to increase the abundance of Clostridiales, Lachnospiraceae, Lactobacillus, Prevotella, and Ruminococcus.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Although no effect on sensitizing markers was detected, signi cantly increased expressions of Foxp3, TGF-β, and IL-10 ileum genes were observed, as well as increased levels of the tryptophan metabolite kynurenine (19). Feeding Bi dobacterium longum to foodallergic mice reduced IL-17 levels (20).…”
Section: Discussionmentioning
confidence: 92%
“…Escherichia Shigella , belonging to the family Enterobacteriaceae, was one of the culprits of acute diarrhea in intestinal infection, which explained severe diarrhea symptoms in GS mice. It has been reported that Escherichia Shigella was significantly increased in OVA-sensitized mice …”
Section: Discussionmentioning
confidence: 99%